Political dispute management in Malaysia: The Islamic legal framework - Oseni, Umar Aimhanosi (2013)
In the bid to discover the past and chart a sustainable future for peaceful co-existence in Malaysia, there is a need to look inwards to develop a framework for political dispute management (PDM). It is pertinent to note that researches on alternative dispute resolution (ADR) have mushroomed over the years but the aspect of PDM has attracted less attention for obvious reasons. Rather than fanning the embers of political division among people of the same communal, cultural and religious backgrounds, this study explores the Islamic legal framework for PDM. The concept of PDM being proposed in this study has two major aspects: dispute avoidance and dispute resolution as clearly provided in Islamic law. Given the fact that the Islamic legal framework is premised on core Shari‘ah principles, the study utilizes the concept of wasatiyyah in addressing the relevant issues. Some of the pertinent issues the study seeks to address include the importance of the Islahi discourse and the role of institutions that are apparently neutral in advancing the cause of PDM through reconciliation and mediation. Bridging the trans-political bride of communication, particularly among Muslims, who, as a result of political affiliations become sworn enemies, is of paramount importance in the modern Malaysian society.